Data in support of comparative physiology and proteomic analysis of two wheat genotypes contrasting in drought tolerance - Elham Faghani (Data in Brief, 2015)
Here, we present the data from a comparative physiology and proteomics approach used to analyze the response of two wheat genotypes (SERI M 82 (SE) and SW89.5193/kAu2 (SW)) with contrasting responses to drought stress. Proteomic analysis resulted in identification of 49 unique proteins with significant change in abundance (2-fold) under water shortage in roots and leaves. Gene ontology analysis of drought-responsive proteins (DRPs) suggested an induction of proteins related to cell wall biogenesis, ATP synthesis, photosynthesis, and carbohydrate/energy metabolism in leaves under stress condition. A large fraction of root proteins were identified to be involved in defense and oxidative stress response. In addition, a significant change was detected in proteins related to protein synthesis, ATP synthesis, and germin-like proteins in response to drought stress. A detailed analysis of this data may be obtained from Ref. [1].